1991
DOI: 10.1055/s-2006-960196
|View full text |Cite
|
Sign up to set email alerts
|

Compounds Inhibiting Prostaglandin Synthesis Isolated fromIpomoea pes-caprae

Abstract: The crude extract (IPA) of the plant Ipomoea pes-caprae (L.) R. Br. showed an inhibitory effect on prostaglandin synthesis in vitro. Bioassay-guided separation of the extract led to the isolation of four active compounds: 2-hydroxy-4,4,7-trimethyl-1(4H)-naphthalenone (1), (-)-mellein (2), eugenol (3), and 4-vinyl-guaiacol (4). Among the isolated compounds, 3 and 4 were the most active with IC50 values of 9.2 and 18 microM, respectively. For 1 and 2 the IC50 values were 230 and 340 microM, respectively. The inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
2

Year Published

1997
1997
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 5 publications
2
36
0
2
Order By: Relevance
“…Externamente, a pasta das folhas é aplicada para o tratamento de queimaduras, especialmente causadas pelo veneno de água-viva (Wasuwat, 1970). Além disso, foi demonstrado que o extrato metanólico da planta exibe efeito espasmolítico em preparações de músculo liso (Emendorfer et al, 2005), confirmando os resultados obtido anteriormente (Pongprayoon et al, 1989(Pongprayoon et al, , 1991a(Pongprayoon et al, , b, 1992. Estudos pré-clínicos em camundongos (Krogh et al, 1999;De Souza et al, 2000) validaram as propriedades analgésicas da planta, confirmando que os flavonóides e terpenos são os principais princípios ativos.…”
Section: Introductionunclassified
“…Externamente, a pasta das folhas é aplicada para o tratamento de queimaduras, especialmente causadas pelo veneno de água-viva (Wasuwat, 1970). Além disso, foi demonstrado que o extrato metanólico da planta exibe efeito espasmolítico em preparações de músculo liso (Emendorfer et al, 2005), confirmando os resultados obtido anteriormente (Pongprayoon et al, 1989(Pongprayoon et al, , 1991a(Pongprayoon et al, , b, 1992. Estudos pré-clínicos em camundongos (Krogh et al, 1999;De Souza et al, 2000) validaram as propriedades analgésicas da planta, confirmando que os flavonóides e terpenos são os principais princípios ativos.…”
Section: Introductionunclassified
“…Preliminary results of chemical investigation of Ipomoea pes caprae showed that the extract contains phenolic and terpenoid substances (Pongprayoon et al, 1991a). In vitro assay detected 2-hydroxy-4,4,7-trimethyl-1(4H)-naphthalenone, mullein, eugenol and 4-vinylguaiacol isolated from I. pes caprae that had inhibitory effect on the synthesis of prostaglandin (Pongprayoon et al, 1991b). New experiments may be assayed to purify and identify the structure of the active principle (s) present in the Ipomoea imperati extract.…”
Section: Discussionmentioning
confidence: 99%
“…Eugenol and guaiacol are also reported to inhibit leukocyte chemotaxis and prevent the production of oxygen free-radicals by leukocytes (Pongprayoon et al, 1991a). Others chemical studies related that I. pes-caprae contains phenolic and terpenoid substances that must to assure the antioxidative activity (Pongprayoon et al, 1991b). I. cairica in its turn, showed that di-O-caffeoylquinic acids also present antioxidative effects (Ferreira et al, 2006).…”
Section: Discussionmentioning
confidence: 99%